Elucidating the pathogenic and biomarker potentials of FOXG1 in glioblastoma - Seidu A. Richard; Zhou Jia-hao (Frontiers Media S.A., 2020)
Glioblastoma (GB) is an extremely pugnacious brain cancer originating from neural stem (NS) cell-like cells. Forkhead box G1 (FOXG1; previously recognized as BF-1, qin, Chicken Brain Factor 1, or XBF-1 and renamed FOXG1 for mouse and human, and FoxG1 for other chordates) is an evolutionary preserved transcription factor driven from the forkhead box group of proteins FOXG1 modulates the speed of neurogenesis by maintaining progenitor cells in a proliferative mode as well as obstructing their differentiation into neurons during the initial periods of cortical formation. FOXG1 has been implicated in the formation of central nervous system (CNS) tumors and precisely GBs. Pathophysiologically, joint actions of FOXG1 and phosphatidylinositol- 3-kinases (PI3K) intermediate in intrinsic resistance of human GB cells to transforming growth factor-beta (TGF-β) stimulation of cyclin-dependent kinase inhibitor 1(p21Cip1) as well as growth inhibition. FOXG1 and NOTCH signaling pathways may functionally interrelate at different stages to facilitate gliomagenesis. Furthermore, FoxG1 actively contributed to the formation of transcription suppression complexes with corepressors of the Groucho/transducin-like Enhancer of split (Gro/TLEs). Also, FOXG1 was stimulated by Gro/TLE1 and abridged by Grg6. FOXG1 silencing in brain tumor-initiating cells (BTICs) also resulted in diminished secretion of markers characteristic undifferentiated natural neural stem/progenitor cells (NSPC) states, such as Oligodendrocyte transcription factor (OLIG2), (sex determining region Y)-box 2. (SOX2) and B lymphoma Mo-MLV insertion region 1 homolog (BMI1). This review therefore focuses on the pathogenic and biomarker potentials of FOXG1 in GB.